2021
DOI: 10.1002/bit.27788
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐scale production of the sesquiterpene α‐humulene with Cupriavidus necator

Abstract: Terpenoids have an impressive structural diversity and provide valuable substances for a variety of industrial applications. Among terpenes, the sesquiterpenes (C 15 ) are the largest subclass with bioactivities ranging from aroma to health promotion. In this article, we show a gram-scale production of the sesquiterpene α-humulene in final aqueous concentrations of 2 g L −1 with the recombinant strain Cupriavidus necator pKR-hum in a fed-batch mode on fructose as carbon source and n-dodecane as an extracting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It is also currently considered suitable for the construction of natural product-like compounds through diversity-directed synthesis; using natural products as a starting point in this process is an emerging strategy for constructing diverse backbones to meet the need for high-throughput screening in drug development [ 32 ]. As part of the pepper scent, the sesquiterpenes, such as α-humulene and germacrene D, which make up the biggest subgroup of terpenes, also have biological properties that are beneficial to health [ 33 , 34 ]. α-humulene has specifically been shown to have anti-inflammatory and anti-cancer activities, with great potential for medical applications [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also currently considered suitable for the construction of natural product-like compounds through diversity-directed synthesis; using natural products as a starting point in this process is an emerging strategy for constructing diverse backbones to meet the need for high-throughput screening in drug development [ 32 ]. As part of the pepper scent, the sesquiterpenes, such as α-humulene and germacrene D, which make up the biggest subgroup of terpenes, also have biological properties that are beneficial to health [ 33 , 34 ]. α-humulene has specifically been shown to have anti-inflammatory and anti-cancer activities, with great potential for medical applications [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpenes (C15), the largest subgroup of terpenoids, has a wide application in industry, such as β-farnesene, a precursor for a jet fuel additive, and α-humulene, a potential drug to treat cancer. Milker et al obtained 26.3 ± 1.3 µM β-farnesene [ 173 ] and 2 g/L α-humulene [ 174 ] in a fed-batch mode on fructose as carbon source by expressing β-farnesene synthase and α-humulene synthase, respectively. Both studies showed that additional MVA expression contributed little to increase the titer of terpenoids, which might be resulted from the poor expression of hydroxymethylglutaryl-CoA reductase ( hmgR ).…”
Section: Synthetic Biology Applications Of C Necator H16mentioning
confidence: 99%
“…With the fast development of synthetic biology, the engineered microbial cell factory was gradually considered to be a promising strategy to produce a variety of high‐value compounds on an industrial scale, including α‐humulene. Previous studies mainly focused on engineered Escherichia coli , Saccharomyces cerevisiae , and Cupriavidus necator for heterologous α‐humulene production (Alemdar et al, 2017; Arnesen et al, 2020; Harada et al, 2009; Krieg et al, 2018; Milker et al, 2021; Sonntag et al, 2015; Zhang et al, 2018, Zhang et al, 2020). However, α‐humulene titer in these engineered microbes was still too low (~2 g/l).…”
Section: Introductionmentioning
confidence: 99%
“…necator for heterologous α-humulene production (Alemdar et al, 2017;Arnesen et al, 2020;Harada et al, 2009;Krieg et al, 2018;Milker et al, 2021;Sonntag et al, 2015;Zhang et al, 2018, Zhang et al, 2020. However, α-humulene titer in these engineered microbes was still too low (~2 g/l).…”
mentioning
confidence: 99%